Magnetic-responsive doxorubicin-containing materials based on Fe3O4 nanoparticles with a SiO2/PEG shell and study of their effects on cancer cell lines - Demin, Alexander M.; Vakhrushev, Alexander V.; Pershina, Alexandra G.; Valova, Marina S.; Efimova, Lina V.; Syomchina, Alexandra A.; Uimin, Mikhail A.; Minin, Artem S.; Levit, Galina L.; Krasnov, Victor P.; Charushin, Valery N. (International journal of molecular sciences)
Novel nanocomposite materials based on Fe3O4 magnetic nanoparticles (MNPs) coated with silica and covalently modified by [(3-triethoxysilyl)propyl]succinic acid-polyethylene glycol (PEG 3000) conjugate, which provides a high level of doxorubicin (Dox) loading, were obtained. The efficiency of Dox desorption from the surface of nanomaterials under the action of an alternating magnetic field (AMF) in acidic and neutral media was evaluated. Their high cytotoxicity against tumor cells, as well as the drug release upon application of AMF, which leads to an increase in the cytotoxic effect, was demonstrated.